Berbagi Nilai Modal Relasional Sebuah Upaya Untuk Meningkatkan Kinerja Pemasaran Usaha Kecil Dan Menengah Di Kota Semarang - Sukrisno Sukrisno; Henry Yuliamir; Enik Rahayu; Bambang Guritno; Haniek Listyorini; Julian Andriani Putri (UNIVED Press, 2022)
This study aims to develop an empirical research model based on the synthesis of a new concept called sharing the value of relational capital. The new concept generated in this study is expected to be able to provide a key role for research solving the influence of entrepreneurial orientation on the marketing performance of MSMEs in the city of Semarang. With a quantitative research design, this study tested the empirical research model on existing MSME industries in the city of Semarang by using 130 research samples. Data analysis was carried out using Amos 25. The results of this study showed that all the hypotheses proposed in this research model were accepted as indicated. with the statistical significance of testing using the software. This study has limitations, including not being able to define specifically the organizational culture environment. In addition, the sample used is only limited to organizations engaged in the manufacturing industry in the province of Central Java. Specifically, the role of the new concept of sharing the value of relational capital can be used as a key strategy for improving the marketing performance of SMEs.